Revitalisasi Nila Kearifan Lokal (Duka Se Cinta) Sebagai Sumber Belajar IPS di SMP Negeri 13 Kota Ternate - Zulkifli, Zulkifli (Jurnal Ilmiah Wahana Pendidikan, 2023)
The aim of this research is to determine and analyze the role of social studies teachers in utilizing local wisdom values as a learning resource at SMP Negeri 13 Tenrate City, to revitalize the value of local wisdom "Bobaso Se Rasai" as a social studies learning resource which can provide knowledge for students, so the delivery of material by social studies teachers not just to focus on existing books, but there is a collaboration of the material taught with the real conditions that students have faced in the social environment. Therefore, social studies learning can be structured in an integrated manner, and has the aim that students gain a broader and deeper understanding and analyze the problems of social life which cannot be separated from everyday life, therefore, students are the next generation of the nation and regions that have the responsibility to maintain and preserve the culture and values of local wisdom of local indigenous communities are intended to ensure that the younger generation or participants continue to uphold what their ancestors have brought to their daily lives in harmony and peace